The Effect of Using Jigsaw Type II Technique on Junior High School Students’ Reading Comprehension Achievement - Muhammad Agradean Triyono; Utari Praba Astuti; Siti Muniroh (South Sulawesi Education Development (SSED), 2024)
The purpose of this study was to analyze the effect of using Jigsaw Type II Technique on reading comprehension achievement of junior high school students. A quasi-experimental design with post-test only design was used to investigate whether there is a significant effect of using Jigsaw Type II Technique on the Reading Comprehension Achievement of Junior High School Students at SMP 1 Kedungjajang. The total number of research participants was 51 students. The experimental class consisted of 25 students and the control class consisted of 26 students. The research participants were selected using cluster random sampling by lottery based on the homogeneity test results. Class VII A (25 students) was designated as the experimental class and class VII C (26 students) was designated as the control class. The data for this study were collected from students' reading comprehension tests, interviews and documentation. The reading comprehension test results were collected and analyzed using the independent sample t-test formula through the SPSS computing system. The result of this study is that there is a significant effect of using Jigsaw Type II Technique on the reading comprehension achievement of junior high school students. The findings of this study provide pedagogical and empirical implications. Pedagogically, English teachers can consider using Jigsaw Type II in teaching reading comprehension because it can provide positive effects during the teaching and learning process.